Excellence in business communication - Thill, John V.; Bovee, Courtland L. (New Jersey : Prentice-Hall International, 1997)
Business
Keywords: Business communication; Business writing; Communication technology; Letter; Memo; Message; Report; Proposal; Employment message; Oral communication